2002
DOI: 10.1192/bjp.181.5.406
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and cognitive decline in elderly people

Abstract: BackgroundDepressive symptoms are associated with cognitive decline in elderly people, but the nature of their temporal relationship remains equivocal.AimsTo test whether depressive symptoms predict cognitive decline in elderly people with normal cognition.MethodThe Center for Epidemiologic Study depression scale (CES – D) and the Mini-Mental State Examination (MMSE) were used to evaluate depressive symptomatology and cognitive functioning, respectively. A sample of 1003 persons aged 59–71 years and with a MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
163
4
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(191 citation statements)
references
References 23 publications
16
163
4
8
Order By: Relevance
“…Estes nossos resultados não corroboram com os estudos de Bourgeois e colaboradores (2015) que, ao explorar o impacto do consumo crónico das BZD´s sobre o declínio cognitivo de uma amostra de idosos institucionalizados constataram que, embora o funcionamento cognitivo dos sujeitos medido através do MMSE se deteriore ao longo do tempo, essa diferença não foi estatisticamente signi cativa entre os sujeitos que consomem BZD´s em relação aos que não consomem. Ainda assim, está bem patente na literatura que o uso prolongado de BZD´s constitui num fator de risco no aumento do declínio cognitivo em pessoas idosas (Bierman et al 2007;Moura, 2014;Paterniti, Dufouil & Alpérovitch, 2002;Zhang et al 2016) e, consequentemente, num aumento da incidência do desenvolvimento de perturbações neurocognitivas como a demência (Gage et al 2012;Gallacher, et al 2012), principalmente a Demência de Alzheimer (Rosenberg et al 2012). Paralelamente não foram encontradas diferenças signi cas entre o consumo de BZD´s e a sintomatologia depressiva medida pela GDS-15 (r pb = .118 , p<.528) e a sintomatologia ansiógena mediante os resultados obtidos GAI-SF(r pb = .130 , p<.486).…”
Section: Resultsunclassified
“…Estes nossos resultados não corroboram com os estudos de Bourgeois e colaboradores (2015) que, ao explorar o impacto do consumo crónico das BZD´s sobre o declínio cognitivo de uma amostra de idosos institucionalizados constataram que, embora o funcionamento cognitivo dos sujeitos medido através do MMSE se deteriore ao longo do tempo, essa diferença não foi estatisticamente signi cativa entre os sujeitos que consomem BZD´s em relação aos que não consomem. Ainda assim, está bem patente na literatura que o uso prolongado de BZD´s constitui num fator de risco no aumento do declínio cognitivo em pessoas idosas (Bierman et al 2007;Moura, 2014;Paterniti, Dufouil & Alpérovitch, 2002;Zhang et al 2016) e, consequentemente, num aumento da incidência do desenvolvimento de perturbações neurocognitivas como a demência (Gage et al 2012;Gallacher, et al 2012), principalmente a Demência de Alzheimer (Rosenberg et al 2012). Paralelamente não foram encontradas diferenças signi cas entre o consumo de BZD´s e a sintomatologia depressiva medida pela GDS-15 (r pb = .118 , p<.528) e a sintomatologia ansiógena mediante os resultados obtidos GAI-SF(r pb = .130 , p<.486).…”
Section: Resultsunclassified
“…Second, depression occurs more frequently in people with diabetes [73] and is difficult to differentiate clinically from dementia and early cognitive decline [74][75][76][77]. However, at least one of the studies [54] reported an association between diabetes and cognitive decline even after adjustment for depression.…”
Section: Discussionmentioning
confidence: 99%
“…This was hinted at by one of the carer"s comments ("he needs to go out") and another who thought that if her spouse did not go out "he would get really depressed". It seems likely that a reduction in a person"s normal use of the outdoor environment can heighten the risk of depression that dementia already poses (Paterniti, Verdier-Taillefer, Dufouil and Alperovitch, 2002). …”
Section: Discussionmentioning
confidence: 99%